Peter Goodrich és a Satirical Legal Studies - Bereznay, Gábor (Debreceni Jogi Műhely, 2006)
Satirical Legal Studies is a study by Peter Goodrich, written in 2005. It was published in Michigan Law Review. I wrote my essay with the purpose of analyzing the main points of this study because – as I know – it has not been translated or published in Hungarian yet.Goodrich gives a comprehensive analysis of the history of the satirical genres, making comparisons, revealing the most important characteristics of these kind of writings. It is the function that distinguishes simple humour from satire and especially legal satire. Satire uses humour as a tool for pointing out to relevant legal matters that need to be changed, so it can easily be admitted that the purpose of satire is reform itself. It means also that the satirical tendencies in jurisprudence have always become stronger in times of need for reforms but we can state that independent of this satire has (more or less) always been present throughout the history of jurisprudence.  Satire has classical, antique traditions that show us the connections between satire and politics or literature. The literary vein of satire or legal satire is less radical than the other one which is in close connection with politics. The latter, more radical form is called Menippean satire and the style of it has always been a certain call for reforms, it always represented a certain social urge to change some relevant legal matters.The study deals with the problems of metaphysical nonsenses in the territory of law, such as for example law would be God made, or it could be unchangeable. Satirical Legal Studies clearly states that these are all contradictional nonsenses. Besides this Satirical Legal Studies has always represented and fought against the social injustice and the injustice of legal institutions.These main points guide us to the figure of the Bad Man, whom the author, Goodrich features as the immunological power of the society revealing all the serious social affairs waiting for an answer. Taking all these facts into consideration the Bad Man is not a tool for the idea of Bad, what’s more: he is or can be the cure for a society’s illness if the legal system does not ignore him and his voice at all because his decadence is only the decadence of the certain time and place that he is a part of. The role of satire is to face the legal system with the pure reality and needs in order to become adequately reactive.